'Evading the Tax Collector’: Native Responses to the Head Tax in Colonial Njombe, Tanzania, 1920-1960. - Chaula, Peter; Kangalawe, Hezron (Zamani: A Journal of African Historical Studies, 2024)
Tax collection was one of the core preoccupations of the colonial government in Tanganyika (now Tanzania) and other colonies in the Africa that persisted even after independence. Direct taxation formed the basis of colonial taxation in Tanganyika. Head tax was a dominant form of direct taxation with its burden being borne primarily by Africans. This article uses the colonial Njombe District of Tanganyika to explore the responses of the African taxpayers to the head tax. The available data indicates that colonial head tax policies and practices in Njombe elicited varied responses from Africans with covert forms forming the mainstay of resistance. By resisting colonial taxation covertly, the natives were able to evade taxes despite the overwhelming power of the British colonial government. This paper argues that resistance against colonial taxation policies and practices in Njombe represented a broader African resentment against colonial rule in Tanzania. However, not all people resisted the payment of colonial taxes as some people collaborated with the colonial government by paying the taxes. This facilitated their integration into the capitalist economy, as most of them had to seek wage labour to earn money to pay colonial taxes. Building on the primary and secondary sources, this article adds to the existing historiography on colonial taxation by analysing the responses of African taxpayers to the payment of head tax in the previously unexplored area of Njombe.